An in-home intervention of parent-implemented strategies to increase child vegetable intake: results from a non-randomized cluster-allocated community trial - Francine M. Overcash; Zata Vickers; Allison E. Ritter; Traci Mann; Elton Mykerezi; Joseph Redden; Aaron K. Rendahl; Cynthia Davey; Marla Reicks (BMC, 2019)
Abstract Background Less than 2% of children in the U.S., ages 9-13, meet the minimum dietary recommendations for vegetable intake. The home setting provides potential opportunities to promote dietary behavior change among children, yet limited trials exist with child vegetable intake as a primary outcome. Strategies to increase vegetable intake grounded in behavioral economics are no/low cost and may be easily implemented in the home by parents. Methods This non-randomized, controlled study tested whether an intervention of parent-led strategies informed by behavioral economics and implemented within a series of 6 weekly parent-child vegetable cooking skills classes, improved dietary outcomes of a diverse sample of low-income children (ages 9-12) more than the vegetable cooking skills classes alone. The primary outcomes were total vegetable intake, dietary quality (HEI scores), total energy intake, vegetable liking, variety of vegetables tried, child BMI-z score, and home availability of vegetables. Outcome measures were collected at baseline, immediate post-treatment, 6 and 12 months follow-up. Mixed model regression analyses with fixed independent effects (treatment condition, time point and treatment condition x time interaction) were used to compare outcomes between treatment conditions. Results A total of 103 parent/child pairs (intervention = 49, control = 54) were enrolled and 91 (intervention = 44, control = 47) completed the weekly cooking skills program. The intervention did not improve child total vegetable intake. Intervention children increased dark green vegetable intake from immediate post-treatment to 12 months. The number of vegetables children tried increased and mean vegetable liking decreased over time for both control and intervention children. Conclusions Findings from this study suggest that the strategies and the manner in which they were implemented may not be effective in low-income populations. The burden of implementing a number of strategies with potentially higher food costs may have constrained the ability of families in the current study to use the strategies as intended. Trial registration This trial has been retrospectively registered at : #NCT03641521 on August 21, 2018.